Genome-wide study on uveal melanoma patients finds association to DNA repair gene TDP1 - Thomsen, Hauke; Chattopadhyay, Subhayan; Hoffmann, Per; Noethen, Markus M.; Kalirai, Helen; Coupland, Sarah E.; Jonas, Jost B.; Hemminki, Kari; Försti, Asta (Melanoma research, 2020)
Uveal melanoma is a life-threatening disease for which data on germline predisposition are essentially limited to mutations in the BAP1 gene. Many risk factors are shared between uveal melanoma and cutaneous melanoma, and these include fair skin color and light eye color. We carried out a genome-wide association study on 590 uveal melanoma patients and 5199 controls. Using a P-value limit of 10(-5) we identified 11 loci with related odds ratios for the risk alleles ranging from 1.32 to 1.78. The smallest P-value in the overall analysis reached 1.07 x 10(-7) for rs3759710 at 14q32.11, which is intronic to TDP1 (tyrosyl-DNA phosphodiesterase 1). This locus emerged as a genome-wide significant association for uveal melanoma clinical subtypes with any chromosomal aberrations (P = 10(-10)) and presence of epithelioid cells (P = 10(-9)). TDP1 is a DNA repair enzyme capable of repairing many types of DNA damage, including oxidative DNA lesions which may be relevant for uveal melanoma. We additionally wanted to replicate the previous candidate locus for uveal melanoma at chromosome 5p15.33 intronic to the CLPTM1L gene. Our analysis gave an odds ratio of 1.23 (95% confidence interval: 1.09-1.38; P = 0.0008) for the C allele of rs421284 and 1.21 (95% confidence interval: 1.07-1.36; P = 0.002) for the C allele of rs452932. Our data thus replicated the association of uveal melanoma with the CLPTM1L locus. Our data on TDP1 offer an attractive model positing that oxidative damage in pigmented tissue may be an initiation event in uveal melanoma and the level of damage may be regulated by the degree and type of iris pigmentation.